Understanding accounting as a career: an immersion work experience for students making career decisions. (2nd January 2016) - McGrath, Dianne; Murphy, Daniel
ABSTRACT: This paper reports on a project which is designed to increase the participation of high school students in accounting work experience placements. The focus of the paper is on an Australian-based project which overcomes the identified barriers to offering high school accounting work experience placements with a resultant increase in the number and quality of placements offered. The research project responds to a decline in both the number and quality of students enrolling in accounting degree programmes in Australia. The paper draws on the work experience, social psychology, careers, and accounting education literatures to design a 'connective' model (Guile & Griffiths, 2001 ) of accounting work experience for high school students. The project adopts an action research methodology which engages professional accounting practice, high school career advisors, and the university sector to deliver a structured work experience programme which addresses barriers to participation in accounting work experience and improves the quality of the work experience 'experience' for both employers and students.